2016
DOI: 10.1038/jp.2016.166
|View full text |Cite
|
Sign up to set email alerts
|

The effects of human milk fortification on nutrients and milk properties

Abstract: Nutrient composition of HM varies significantly by milk type. Although fortifiers enhance select nutrients, each has the potential to affect HM properties in a unique way and these affects may vary by milk type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 29 publications
2
33
1
1
Order By: Relevance
“…This finding contrasts with some earlier studies that reported increases in osmolality of fortified EHM after storage. 8,12,13 However, those studies used a variety of other fortifiers, for periods of storage ranging from 24 to 72 hours. Moreover, the reported changes in osmolality were consistently small (10 mOsm/kg, or 3%-4%).…”
Section: Discussionmentioning
confidence: 99%
“…This finding contrasts with some earlier studies that reported increases in osmolality of fortified EHM after storage. 8,12,13 However, those studies used a variety of other fortifiers, for periods of storage ranging from 24 to 72 hours. Moreover, the reported changes in osmolality were consistently small (10 mOsm/kg, or 3%-4%).…”
Section: Discussionmentioning
confidence: 99%
“…One of the major differences in ELHMF, in comparison to SLHMF, is the level of acidification of ELHMF (pH: 4.82-5.1 vs. 6.21-6.53). 20 We observed a probable clinical translation of this difference resulting in a significant metabolic acidosis in the ELHMF group. Previous investigators have also reported observations along these same lines.…”
Section: Discussionmentioning
confidence: 63%
“…Recently, Donovan et al has also shown that the lipase activity in HM fortified with EHLMF is approximately 8% lower than SLHMF. 20 Our findings of relatively poor weight gain in the ELHMF group can be explained by the decreased bioavailability of both protein and lipids in these preterm babies. We relied, as previous researchers, on the manufacturer's data on calorie and protein intake in the breast milk and HMF.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…A alta variação nutricional existente no leite de cada mãe também desafia a fortificação padrão já conhecida com as fórmulas à base de proteína heteróloga, que podem aumentar a ocorrência de intolerância alimentar e enterocolite necrotizante. (ROCHOW et al, 2015) (DONOVAN et al, 2017 Há uma crescente tendência na análise bed side do leite humano nas Unidades de Terapia Intensiva Neonatais, apesar de ser uma tecnologia de alto custo. São utilizados analisadores de leite humano por infravermelho que fornecem uma análise rápida do leite materno para conhecer o seu conteúdo de macronutrientes e adaptar essa fortificação que pode ser benéfica para o recém-nascido.…”
Section: Discussionunclassified